Case Study: The Effect of Live Sessions on Student Success in Online Education - Ademi, Neslihan; Loshkovska, Suzana (IEEE, 2023)
Learning Management Systems (LMSs) are commonly used in modern education settings as they offer many opportunities to students and tutors in distance learning settings. Moodle is one of the most popular free and open source LMSs. It stores all students' online activities in the log files, which allows the knowledge extraction by Educational Data Mining applications. BigBlueButton is an open-source web conferencing system for online learning which can be integrated into Moodle. This study presents the effect of students' attendance at online live sessions and the changes in the student success when the formal education evolved from blended learning to fully online learning during the pandemic period. It involves the analysis of Moodle log data collected from five years of studies, comparing the success in different learning settings: blended, online, online with live sessions and online with badge application. Analysis performed on the logs show that points gained by the students are highly associated with their attendance at online live classes and the recording views.
Keywords: Learning Management Systems; Distance Learning; Moodle logs; Educational Data Mining; BigBlueButton